A Official Vehicle Movement Monitoring System Using Dijkstra's Algorithm on GPS and Real-Time Notifications: Journal Poltekad, Vol, SIPAKAD vehicle movement monitoring. - yuslan, mohammad; Derius, Desy (Pustaka Poltekad, 2025)
Official vehicle management requires an efficient, accurate, and integrated monitoring system to support transparent and responsive operations. This research aims to design and implement a Police Department Vehicle Management Information System (SIPAKAD) based on GPS, the Dijkstra algorithm, and Firebase Cloud Messaging (FCM). The research method used was an experimental quantitative approach, through software development that was repeatedly tested to obtain actual data. The independent variables in this study were the use of GPS, the Dijkstra algorithm, webhooks, and FCM, while the dependent variables included vehicle monitoring efficiency, optimal travel time, and operational response speed. The results showed that the integration of GPS with the Dijkstra algorithm was able to display vehicle positions in real time while providing recommendations for the shortest route visualized on a digital map. A comparison between the algorithm-calculated route and the actual GPS data revealed very small differences in distance and travel time. Accuracy evaluation using the Mean Absolute Percentage Error (MAPE) resulted in a low error value, demonstrating the system's accuracy and reliability. Furthermore, FCM integration allows for automatic notification of departure, arrival, and emergency status (SOS) instantly to drivers and administrators. This feature improves communication effectiveness, accelerates decision-making, and enhances operational safety. Thus, this research successfully presents a superior official vehicle monitoring system compared to previous research, integrating real-time position monitoring, route optimization, instant notifications, and safety features in a single platform. SIPAKAD is expected to become an applicable solution that supports efficiency, security, and transparency in the management of official vehicles and other sectors with similar needs.